Unintended side effects of unconventional monetary policy - Tobias Berg; Rainer Haselmann; Thomas Kick; Sebastian Schreiber (Goethe University, Center for Advanced Studies on the Foundations of Law and Finance (LawFin), 2022)
Using granular supervisory data from Germany, we investigate the impact of unconventional monetary policies via central banks' purchase of corporate bonds. While this policy results in a loosening of credit market conditions as intended by policy makers, we document two unintended side effects. First, banks that are more exposed to borrowers benefiting from the bond purchases now lend more to high-risk firms with no access to bond markets. Since more loan write-offs arise from these firms and banks are not compensated for this risk by higher interest rates, we document a drop in bank profitability. Second, the policy impacts the allocation of loans among industries. Affected banks reallocate loans from investment grade firms active on bond markets to mainly real estate firms without investment grade rating. Overall, our findings suggest that central banks' quantitative easing via the corporate bond markets has the potential to contribute to both banking sector instability and real estate bubbles.
urn:nbn:de:hebis:30:3-616663
Keywords: 330